Experimental Investigation on Effects of Bacterial Concentration, Crack Inclination Angle, Crack Roughness, and Crack Opening on the Fracture Permeability Using Microbially Induced Carbonate Precipitation - Yulin Zou; Hao Bai; Fan Shen; Hong Xu; Yundong Shou (Advances in Civil Engineering)
Uncontrollable leakage has significant effects on the safety of fractured rock mass, and microbially induced carbonate precipitation (MICP) is an effective way to control the seepage. In this study, four sets of seepage experiments are conducted on transparent rock-like specimens containing MICP filled single cracks to investigate the effects of bacterial concentration, crack inclination angle, crack roughness, and crack opening on fracture permeability. The experimental results show that calcium carbonate precipitation is produced when Sporosarcina pasteurii and cementing fluid are injected into the cracks, which can seal the cracks and reduce the permeability of the cracks. Moreover, the calcium carbonate produced by Sporosarcina pasteurii increases with increasing bacterial concentration. Furthermore, the fracture permeability of the MICP filled crack increases first and then decreases with increasing inclination, roughness, and opening of cracks. The experimental results provide a better understanding of the influence of different construction conditions on fracture permeability when the MICP technology is applied in rock engineering.